The Use of ITS for Improving Bus Priority at Traffic Signals - Morellato, Camilla; Sdun, Mathias (Proceedings from the Annual Transport Conference at Aalborg University, 2010)
A modal shift from private to public transport, which will lighten traffic congestion and environmental impact, can be achieved only if bus service is made more efficient and attractive to passengers. One of the ways to achieve the goal is to exploit Intelligent Transport Systems (ITS) within public transport. This paper examines the potential of ITS for improving bus priority at traffic signals, based on comparison and analyses of different bus priority systems, aiming at detecting weaknesses and strengths of each of them. Moreover, a framework for the evaluation of bus priority systems is presented, together with examples of benefits achieved internationally and challenges for research.